ADVANCED DOB-BASED MOTION AND TRACTION CONTROL OF A DIFFERENTIALLY WHEEL NON-HOLONOMIC MOBILE ROBOT - Kenzhekhan, Azamat (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Differentially driven mobile robots are used in a diverse range of applications, varying from pipe inspections, space exploration, investigation of chemical contamination of hazardous environments, industrial automation, service robots, autonomous vehicles, education, and even household machines. However, guaranteeing accurate and stable control under various uncertainties, such as changes in payload, friction, or terrain irregularities, is a major challenge. Robust control methods are necessary for these types of challenges, and one of the most assuring approaches is Disturbance Observer (DOB) Control. DOB has gained attention due to its ability to estimate and compensate for external disturbances, which enhances the performance and stability of control systems. In this study, a DOB-based motion control setup was tested on a four-wheeled mobile robot, both in simulation and real experiments. The robot was pushed to operate under heavier-than-usual loads—up to 46 kg—on smooth and slippery indoor floors. The results proved the effectiveness of DOB for mobile robots, which opens up the doors for other wheeled devices like electric vehicles, etc.
Keywords: Mobile Robot; Disturbance Observer; Traction control; type of access: embargo